2021
DOI: 10.3390/land10040377
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Characteristics in Reducing the Inventory of Unsold Housing in New Residential Developments—A Case of Gyeonggi Province, in South Korea

Abstract: This study analyzes the effect of green characteristics on sales of unsold housing stock, using a multilevel growth model, in Gyeonggi Province, South Korea from 2012 to 2018. The green characteristics we estimated are external factors such as the proximity to urban parks and mountain trails located outside the housing complex and internal factors such as whether the area of communal open space within the complex exceeds a certain percentage. The results suggest that potential home-buyers are interested in gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The findings form the current study found that distance of the Unsold New Houses to the nearest markets or shopping mall (B = 0.534, P < 0.05) was a significant predictor of the duration of unsold new houses. The results support findings of a study conducted by Yoo et al (2021) investigating how locational factors affected unsold unit ratio that concluded that the proximity to the shopping malls were positively associated with the reduction of unsold units. The results also support the findings of Majelan et al (2020) that concluded that good location is associated with high demand and location was a major factor when choosing an affordable housing since homebuyers usually look for strategic housing close to the city center, shopping malls and work place since this offers convenience to homebuyers in terms of distance, travel time and cost.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…The findings form the current study found that distance of the Unsold New Houses to the nearest markets or shopping mall (B = 0.534, P < 0.05) was a significant predictor of the duration of unsold new houses. The results support findings of a study conducted by Yoo et al (2021) investigating how locational factors affected unsold unit ratio that concluded that the proximity to the shopping malls were positively associated with the reduction of unsold units. The results also support the findings of Majelan et al (2020) that concluded that good location is associated with high demand and location was a major factor when choosing an affordable housing since homebuyers usually look for strategic housing close to the city center, shopping malls and work place since this offers convenience to homebuyers in terms of distance, travel time and cost.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…The results of their study showed that using concrete or concrete blocks as building materials or having the building prefabricated can reduce the time to market. A study in South Korea by Yoo and Yoon (2021) analyzed the effect of green characteristics on sales of unsold housing stock, using a multilevel growth model, in Gyeonggi Province. The green characteristics that were estimated were external factors such as the proximity to urban parks and mountain trails located outside the housing complex and internal factors such as whether the area of communal open space within the complex exceeds a certain percentage.…”
Section: ~ 54 ~mentioning
confidence: 99%
“…The computational procedure of the green spaces accessibility index is introduced in detail in Appendix A. All the data are computed by the Network Analyst tool in ArcGIS 10.8 6 .…”
Section: Public Urban Green Spaces (Pugs)mentioning
confidence: 99%
“…Factors such as air quality, water pollution, noise levels, and the availability of green spaces have gained significance in shaping healthier and more pleasant urban environments [1][2][3]. Among these factors, the significance of green spaces has garnered considerable attention from both academia and industry, owing to their multifaceted benefits [4][5][6].…”
Section: Introductionmentioning
confidence: 99%